How shape and flapping rate affect the distribution of fluid forces on flexible hydrofoils. (25th October 2020) - Dagenais, Paule; Aegerter, Christof M.
Abstract: Abstract : We address the fluid–structure interaction of flexible fin models oscillating in a water flow. Here, we investigate in particular the dependence of hydrodynamic force distributions on fin geometry and flapping frequency. For this purpose, we employ state-of-the-art techniques in pressure evaluation to describe fluid force maps with high temporal and spatial resolution on the deforming surfaces of the hydrofoils. Particle tracking velocimetry is used to measure the three-dimensional fluid velocity field, and the hydrodynamic stress tensor is subsequently calculated based on the Navier–Stokes equation. The shape and kinematics of the fin-like foils are linked to their ability to generate propulsive thrust efficiently, as well as the accumulation of external contact forces and the resulting internal tension throughout a flapping cycle.